Investigating the Relationship between Knitted Fabric Porosity and Light Permeability. (25th October 2016) - Imrith, Manoj Kumar; Unmar, Roshan; Rosunee, Satyadev
Abstract : The present paper attempts to investigate the relationship between fabric porosity and light permeability of the knitted structures, namely, rib 1 × 1, rib 2 × 1, single jersey, and plain structure. The rationale is that pores (in a fabric) would allow light to pass through but at the same time provide a quantitative assessment of the UV light permeability of the knitted fabrics, an indication of the protective capacity of the fabrics against UV radiation. The porosity and corresponding light permeability of the knitted structures were measured after varying the following knitting parameters: stitch length, stitch density, and tension on the machine. Furthermore, this work has enabled the development of an apparatus that can measure the amount of light transmitted through the knitted fabrics. The results generated by the equipment were validated through the use of regression equations.